The use of didactic games in the course of teaching Health Education» - Drizul A.V (Kharkov National Pedagogical University, 2010)
Practical experience of application of didactic games is analysed in teaching of the article of "Basis of health" (5-9 class). The rotined possibilities and advantages of the use of separate types of games (role, games-trips, games-competitions) are in upgrading teaching, creation of favorable educational environment, forming of healthy way of life for the students of the proper age. Educational discipline of "Basis of health" is presented as a model of primary prophylaxis of violations of health and providing of children necessary knowledge, abilities and skills.